Factors affecting the communication barrier among selected expatriates in Malaysia / Nur Izzati Roslan - Roslan, Nur Izzati (Faculty of Business and Management, 2019)
The purpose of this research is to examine the factors affecting communication barrier among expatriates at workplace. This study consist of three (3) independent variables that are culture differences, organizational structure and communication style. This research is focusing on selected expatriates in Malaysia, specifically in Selangor. 70 sets of questionnaires was distributed to the selected expatriates in Selangor. The questionnaires are using 7 point Likert Scale as instrument. Besides that, this study was analyzed using Statistic Package for Social Science (SPSS) with Descriptive Analysis, Reliability Analysis, Correlation Analysis and Multiple Regression Analysis as data analysis. Based on the result, the two (2) independent variables which are culture differences and organizational structure have a significant relationship with the dependent variable that is barrier of communication among expatriates at workplace. However, there is no significant relationship between communication style and barrier of communication among expatriates at workplace.